2019
DOI: 10.3390/ijms20092085
|View full text |Cite
|
Sign up to set email alerts
|

Unappreciated Role of LDHA and LDHB to Control Apoptosis and Autophagy in Tumor Cells

Abstract: Tumor cells possess a high metabolic plasticity, which drives them to switch on the anaerobic glycolysis and lactate production when challenged by hypoxia. Among the enzymes mediating this plasticity through bidirectional conversion of pyruvate and lactate, the lactate dehydrogenase A (LDHA) and lactate dehydrogenase B (LDHB), are indicated. LDHA has a higher affinity for pyruvate, preferentially converting pyruvate to lactate, and NADH to NAD+ in anaerobic conditions, whereas LDHB possess a higher affinity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
144
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 86 publications
(135 reference statements)
2
144
2
1
Order By: Relevance
“…According to previous studies, an elevated level of LDH isoforms is more common in malignant tumors than normal cells (32). The increased LDH level could promote tumor progression by regulating the tumor metabolism and microenvironment and acts as a poor prognostic indicator for cancer patients (32,33). A meta-analysis investigating the prognostic value of the LDH level in solid tumors showed that a high LDH level is associated with poor survival in melanoma, gastric, lung cancer, prostate, and renal cell carcinomas (34).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to previous studies, an elevated level of LDH isoforms is more common in malignant tumors than normal cells (32). The increased LDH level could promote tumor progression by regulating the tumor metabolism and microenvironment and acts as a poor prognostic indicator for cancer patients (32,33). A meta-analysis investigating the prognostic value of the LDH level in solid tumors showed that a high LDH level is associated with poor survival in melanoma, gastric, lung cancer, prostate, and renal cell carcinomas (34).…”
Section: Discussionmentioning
confidence: 94%
“…According to previous studies, an elevated level of LDH isoforms is more common in malignant tumors than normal cells (32). The increased LDH level could promote tumor progression by regulating the tumor metabolism and microenvironment and acts as a poor prognostic indicator for cancer patients (32,33).…”
Section: Discussionmentioning
confidence: 96%
“…Lactate dehydrogenase (LDH) is a detectable enzyme in the cytoplasm of nearly all cells in the human body, and its extracellular presence is associated with cell necrosis and tissue destruction, since it becomes extracellular due to cell death [27,28]. LDH is an enzyme whose activity is routinely measured clinically, and it has subtypes ranging from LDH-1 to LDH-5 [29]. The isoenzyme profile of LDH activity is different in the saliva and in the blood: while LDH-5 is dominant in the former, LDH-1 is dominant in the latter [30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, LDHA is dysregulated in several cancers including pancreatic cancer, 14,15 breast cancer, 16,17 and glioma, 18 plays a role in the aggressiveness of gastric cancer; 19 and controls apoptosis in some cancer types. 20 Expression of LDHA is speculated to be regulated by a few known factors, including fibroblast growth factor receptor, 21 cyclin G2, 22 FLF4, 23 FOXM1, 24 or through a welldefined MYC-LDHA pathway; 14,25,26 however, there are little data beyond these, particularly in regards to upstream initiators.…”
Section: Introductionmentioning
confidence: 99%